CardioVASS device: For cardiology trainee - Mohd Azrul Hisham, Mohd Adib; Chik Ming, Mok; Nur Afikah, Khairi @ Rosli; Nurul Natasha, Mohd Sukri; Idris, Mat Sahat (2021)
CardioVASS device is a medical device that have been developed to assist the medical training process especially for the cardiology trainee. Our current CardioVASS device are equipped with the latest “Real 3D Monitoring System” that enables the user to experience a real time monitoring system with upgraded electronic and mechanical complete system that ready to be commercialize.